Kritik Politik Dalam Antologi Puisi Manusia Istana Karya Radhar Panca Dahana: Analisis Dan Bentuk Isi - Anastasia P.M., A. A. Istri Dian; Sudewa, I Ketut; Triadnyani, I G.A.A. Mas (Humanis; Volume 17. No. 2. Nopember 2016)
Undergraduate thesis entitled "Political Criticism in Poetry Anthology of Manusia Istana by Radhar Panca Dahana: Analysis of Form and Content" was motivated by theme selection of political criticism that contains aspects of the form and content of the poem. The theme was related to Radhar Panca Dahana’s background as a lecturer of Sociology at Indonesia University. There were two problems formulated, namely: the form and contents of the 15 poems of poetry anthology Manusia Istana by Radhar Panca Dahana. The purpose of this study was to determine the form and contents of the 15 poems of poetry anthology Manusia Istana. This study carried out literature and descriptive analytic method. The technique used was collecting, recording, interpreting and sampling techniques. The analysis was done by conducting several steps. First, analyzing the creative process of Radhar Panca Dahana’s work. Second, analyzing of the form and content of the poetry anthology Manusia Istana. Aspect of form consists of diction, sound, imagery and figurative language. Aspect of content consists of themes and messages. Both aspects were applied in analyzing all 15 poems by Radhar Panca Dahana. Analysis of the 15 poems of poetry anthology Manusia Istana by Radhar Panca Dahana shows that the form and content of poem are important in expressing political critique. The use of diction, sound, imagery and figurative language to convey the poet is able to make the reader imagine and contemplate about the political situation in Indonesia.
Keywords: poetry, form, contents